A Comparitive Study of Non-Perforated and Perforated Appendicitis (Global Journal of Medical Research, 2018)
Acute appendicitis is the commonest surgical emergency. The lifetime incidence of appendicitis is 6-7% and is more in males than in females with maximum incidence in 10-14 year male and 15-19 year female. 1-2 Appendicitis presents as right iliac fossa pain, nausea, vomiting, and decreased appetite. But only 50% of patients present with these classical symptoms. Hence there is delay in diagnosis. The pathophysiology leading to appendicitis is not clear, it is likely that luminal obstruction by external (lymphoid hyperplasia) or internal (inspissated fecal material, appendicoliths) compression plays a key pathogenic role. The luminal obstruction leads to increased mucus production, bacterial overgrowth, and stasis, which increases appendiceal wall tension.